Sistem Rekomendasi untuk Penentuan Konsentrasi pada Informatika Universitas Muhammadiyah Surakarta dengan Fuzzy - Efrina Fitriani; Yogiek Indra Kurniawan (Politeknosains, 2017)
In the determination of Concentration requires a recommendation system as an alternative to taking the decision to vote with the right concentration. The problems faced by students of the Informatics prodi Muhammadiyah University of Surakarta (UMS) in determining the concentration according to his own abilities and interests is very difficult, let alone with a student who is not confident with his ability, follow friends and lack of information known by students about the concentration there is. Therefore, the recommendation system built in this study as one of the alternative attempts to address these problems. Determination of the concentration of established based on several categories/consideration, namely the interest of the students (using questionnaires/question form) and the value of the course (transcriptions) in each concentration. Matlab programming language implementation and research method using fuzzy mamdani. Mamdani's method is the most appropriate method with the penenlitian, because it is simple in structure, i.e. using Min-Max. The data is managed via phase – phase calculation of the fuzzy logic and then give the output in the form of recommendations and the results of the comparison of the student in question. The results of this research in the form of a recommendation system that helps students to determine concentration based on the desired category, as well as the system menghasil accuracy rate of 94.7619% of the data.